PENGARUH MEDIA YOUTUBE PADA PEMEROLEHAN BAHASA B2 ANAK USIA 3 TAHUN - Irwansyah, Ahmad; Shabiburrahman, Saqo (Fakultas Bahasa dan Sastra Indoensia, 2022)
This study aims to explain the acquisition of a second language (B2) in a case study of a child through the social media YouTube. YouTube media can also be used for children who are still at the stage of language acquisition. This study uses a qualitative method and a descriptive approach. This study aims to explain the acquisition of a second language, namely English which focuses on the basic vocabulary of nouns or animal names and basic numerals, namely numbers 1 to 10. Based on the results of this study, it can be seen that YouTube media has a significant influence on the acquisition of a second language (B2) in children. However, YouTube does not fully substitute the human role in language acquisition or learning.